Clinical Association of Thyroid Stimulating Hormone Receptor Antibody Levels with Disease Severity in the Chronic Inactive Stage of Graves' Orbitopathy - Woo, Young Jae; Jang, Sun Young; Lim, Tyler Hyung Taek; Yoon, Jin Sook (Korean journal of ophthalmology, 2015)
To investigate associations between serum thyroid stimulating hormone (TSH) receptor antibody (TRAb) levels and Graves' orbitopathy (GO) activity/severity in chronic-stage GO and compare the performance of two newly-developed TRAb assays (third-generation TSH-binding inhibition immunoglobulin [TBII] assay versus Mc4 thyroid-stimulating immunoglobulin [TSI] bioassay). This study is a retrospective review of medical charts and blood tests from Korean GO patients who first visited the departments of ophthalmology and endocrinology, Yonsei University College of Medicine from January 2008 to December 2011, were diagnosed with GO and Graves' hyperthyroidism, and were followed up for ≥18 months. Third-generation M22-TBII and Mc4-TSI assays were performed in the chronic-inactive GO patients in whom euthyroidism status was restored. Patients' GO activity/severity clinical activity scores (CAS), and modified NOSPECS scores were examined for a correlation with TRAb assays. Fifty patients (mean age, 41.3 years; 41 females) were analyzed. The mean duration of Graves' hyperthyroidism symptom was 63 months (range, 18 to 401 months) and that of GO was 46 months (range, 18 to 240 months). All patients had been treated previously with anti-thyroid drugs for a median period of 52.3 months, and two patients underwent either radioiodine therapy or total thyroidectomy. Mean CAS and NOSPECS scores were 0.5 ± 0.9 (standard deviation) and 4.8 ± 3.1, respectively. Mean M22-TBII and Mc4-TSI values were 7.5 ± 10.2 IL/L and 325.9 ± 210.1 specimen-to-reference control ratio. TSI was significantly correlated with NOSPECS score (R = 0.479, p < 0.001); however, TBII was not associated with NOSPECS score (p = 0.097). Neither TSI nor TBII correlated with CAS (p > 0.05), because GO inflammatory activity subsided in the chronic stages of GO. In chronic-inactive GO after euthyroid restoration, GO activity score did not associate with serum levels of TRAb or TBII. However, levels of the functional antibody Mc4-TSI did correlate with GO severity. Therefore, the TSI bioassay is a clinically relevant measure of disease severity even in chronic inactive GO.